FAKTOR YANG MEMPENGARUHI PERSEPSI SISWA TENTANG PAI SMK NEGERI 3 SAMPIT - Jayadi Jayadi; Norhayatun Norhayatun; Bahagia Bahagia (STKIP MUHAMMADIYAH SAMPIT, 2019)
student perception about religious education of islami some factors. This research was conducted to determine the factors that influence perception about religious education of islami, with the sample the study were students of class XI SMK Negeri 3 Sampit of 70 students. Methods in this study using quantitative methods. Results of research based student perception about religious education of islami is good enough that dominated enough influenced by psychology factor, family factor and cultural factor with percentage 69%, with number of respondent 48 from total of respondent 70.